PENGARUH TEMPERATUR DAN WAKTU REAKSI PADA KONVERSI KATALITIK RESIDU MINYAK BUMI - Hartiniati, Hartiniati (Jurnal Energi dan Lingkungan (Enerlink), 2008)
A hydroconversion catalytic process of Indonesian petroleum residue from Plaju(UP IV) refinery plant was investigated. A series of liquefaction tests using a 1liter stirred batch autoclave reactor under reference condition e.i.: initial hydrogenpressure of 12 MPa and 2.0 of atomic ratio of sulfur to iron were conducted. Theinfluence of the temperature of 430,450,470oC and the reaction time of 30,60,90minute was used and compare the yield structure of each run. It was found thatthe oil yield and gases CO, CO2 and hydrocarbon yield increased significantly bythe increasing of the temperature reaction and holding time. While, the liquidbottom yield had a tendency to decrease which reversely to the oil yield. It alsoappeared that hydrogen consumption would tend to increase with increasing oilyield, leading to the more efficiently use of gaseous hydrogen. As a result, thehydroconversion catalytic process could be applied to upgrade petroleum residuewhich indicated by increasing oil yield in mild condition.Kata Kunci: hidrokonversi katalitik, residu minyak bumi